Evaluation of the Quality of Academic Information Services on the FEB UNJ Website Based on the WebQual and EUCS Models - Utari, Eka Dewi; Atmadja, Ferry Setyadi; Nida, Ria Rahma; Rabbaniyah, Lathiefah; Ayyun, Dinda Ramadhani Qurrota (Information Technology and Science (ITScience), 2025)
This study aims to evaluate the quality of academic information services provided through the website of the Faculty of Economics and Business, State University of Jakarta (www.feb.unj.ac.id). The research approach used was quantitative descriptive using the WebQual 4.0 model which was modified through the addition of the Eas of Use variable from the End User Computing Satisfaction (EUCS) model. A total of 124 respondents consisting of students and lecturers were involved in this study through the distribution of questionnaires. Data were analyzed using multiple linear regression with the help of SPSS. The results showed that the variables Information Quality and Interaction Quality had a significant influence on user satisfaction, while Usability and Content did not show a statistically significant partial effect. However, simultaneously, the four variables contributed 70.8% to user satisfaction. This study emphasizes the importance of accuracy, trust, and ease of access as the main factors in supporting user satisfaction with website-based academic information services. This research contributes to the development of academic information systems by offering a comprehensive evaluation framework that integrates the WebQual and EUCS models, while also emphasizing the critical roles of information accuracy, user interaction, and ease of access in enhancing user satisfaction thus providing a practical reference for improving the quality of academic websites in higher education institutions in Indonesia.